2021
DOI: 10.20944/preprints202112.0437.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Determinants of Smallholder Households’ Resilience to Livelihood Insecurity in Goncha District, Northwest Highlands of Ethiopia

Abstract: Poor households are more likely less resilient under climate change, risks of productive assets, social-related shocks, and decline of land productivity. The ability to deal with household resilience against poverty under the uncertain condition of risk is limited in the highlands of Ethiopia. The study aims to identify determinants of household resilience to livelihood insecurity under the crop-livestock mixed farming systems in Goncha district, Northwest highlands of Ethiopia. Primary data were collected by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Incentives in the form of compensation for labor as direct economic incentives, either FFW or, in some cases, cash-forwork, were offered by international donors of FFW program in Ethiopia between 1976Ethiopia between and 1988Ethiopia between and 1976Ethiopia between and 1990 Moreover, the bulk of conservation measures in rural areas were physical measures applied to both communal holdings and farmer plots (Demeke, 2003). Additionally, the Fanya-juu terrace's structural measures, which were augmented with vetiver and elephant grass, showed that Fanya-juu with elephant grass produced a higher yield than Fanya-juu with vetiver grass (309.6 g/m 3 ) and unconserved (207.9 g/m 3 ) land (Debie, 2014). Nevertheless, compared to land without those structures, research findings showed that grass strips, bench terraces, and fanya juu all dramatically decreased soil loss by 40%, 76%, and 88%, respectively (Asnake, 2016).…”
Section: Empirical Studies On Watershed Management Soil Quality and P...mentioning
confidence: 99%
“…Incentives in the form of compensation for labor as direct economic incentives, either FFW or, in some cases, cash-forwork, were offered by international donors of FFW program in Ethiopia between 1976Ethiopia between and 1988Ethiopia between and 1976Ethiopia between and 1990 Moreover, the bulk of conservation measures in rural areas were physical measures applied to both communal holdings and farmer plots (Demeke, 2003). Additionally, the Fanya-juu terrace's structural measures, which were augmented with vetiver and elephant grass, showed that Fanya-juu with elephant grass produced a higher yield than Fanya-juu with vetiver grass (309.6 g/m 3 ) and unconserved (207.9 g/m 3 ) land (Debie, 2014). Nevertheless, compared to land without those structures, research findings showed that grass strips, bench terraces, and fanya juu all dramatically decreased soil loss by 40%, 76%, and 88%, respectively (Asnake, 2016).…”
Section: Empirical Studies On Watershed Management Soil Quality and P...mentioning
confidence: 99%